Comparing short‐term/long‐term outcomes of heart transplants that occur inside and outside of normal working hours. (23rd April 2022) - Nishida, Hidefumi; Salerno, Christopher; Onsager, David; Song, Tae; Nguyen, Ann; Grinstein, Jonathan; Chung, Bow; Smith, Bryan; Kalantari, Sara; Sarswat, Nitasha; Kim, Gene; Pinney, Sean; et al.
Abstract: Aims: Heart transplantation involves many factors such as donor selection, recipient management, multidisciplinary assessment, coordination with other organ teams, and transportation. Because of some unpredictable factors, heart transplantation can be conducted at any time of day. The purpose of this study is to investigate if outcomes differ between heart transplants taking place inside or outside of normal working hours. Methods and results: We reviewed patients who underwent heart transplantation at our institution from January 2010 to July 2020 ( n  = 329). Based on the documented start time of the recipient surgeries, the cohort was divided into two groups: working hours (Group A: 7:30 to 17:00; n  = 92) and after hours (Group B: 17:00 to 7:30; n  = 237). We compared these groups using propensity score matching analysis. After propensity score matching, 78 pairs of patients were successfully matched. We reviewed early and late clinical outcomes including survival. Long‐term survival was compared using the Kaplan–Meier method. In the propensity‐score matched patients, there were no significant differences in the baseline characteristics between two groups. In‐hospital mortality was not significantly different between the two groups (Group A: 6.4% vs. Group B: 2.6%, P  = 0.44). Ischaemic time and cross‐clamp time did not differ between the groups. In terms of postoperative complications, there were no significant differences between two groups in stroke (6.4% vs. 3.9%, P  = 0.72), primary graft dysfunction requiring extracorporeal membrane oxygenation (5.1% vs. 7.7%, P  = 0.75), re‐exploration for bleeding (9.0% vs. 12.8%, P  = 0.44), and newly required haemodialysis (7.7% vs. 6.4%, P  = 0.75). The survival rate in Group A (88.1% at 1 year, 81.3% at 3 years) was not significantly different from Group B (90.5% at 1 year, 82.3% at 3 years, log rank = 0.96). Conclusion: There was no significant difference in clinical outcomes between heart transplants taking place inside or outside of working hours. A high quality of care can be provided for heart transplant patients even during after hours.